Enhancing Writing Skills by Using The Project-Based Learning Model Through The Hello Talk Application - Rully Khoeru Solihin; Rudi Hartono; Dwi Rukmini; Sri Wahyuni (International Conference on Science, Education, and Technology, 2023)
This study intends to describe the project-based learning model implementation for learning to write English using the HelloTalk application and to ascertain how students react to the project-based learning model implementation using the HelloTalk application. The technique employed is a qualitative descriptive method, and it entails the process of gathering primary data through document review, field data collection, and the outcomes of student response surveys. 93 students from AKPER YPIB Majalengka's second semester served as the study's subjects. The examination of the data revealed that the student had a very high level of enthusiasm in putting the project-based learning strategy for learning to write in English using the HelloTalk program into practice. The study's findings indicate that the project-based learning model using the HelloTalk application was successfully implemented in teaching students to write in English and received a favorable response from the students. It also indicates that using the project-based learning model with the HelloTalk application can improve students' writing abilities in English. The HelloTalk program for learning to write in English met very high standards.